2021
DOI: 10.1111/ssqu.12955
|View full text |Cite
|
Sign up to set email alerts
|

Are School Reopening Decisions Related to Union Influence?

Abstract: Objective. The COVID-19 pandemic led to widespread school closures affecting millions of K-12 students in the United States in the spring of 2020. Groups representing teachers have pushed to reopen public schools virtually in the fall because of concerns about the health risks associated with reopening in person. In theory, stronger teachers' unions may more successfully influence public school districts to reopen without in-person instruction. Methods. We examine the relationship between teachers' union stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
6
17
0
Order By: Relevance
“…This finding is consistent with the public positions taken by the nation’s two largest unions in supporting their locals’ efforts to delay in-person learning until various public health benchmarks are met. It is also consistent with several other recent studies showing that teachers unions have influenced district reopening decisions, largely slowing the pace at which in-person learning has resumed (DeAngelis and Makridis forthcoming; Grossman et al 2021; Harris et al 2021). Although we are confident that district size is a reasonable proxy for union strength, we acknowledge that the size of a school district itself is also likely to present different logistical challenges that may shape a district’s practical choice in a reopening plan.…”
Section: Resultssupporting
confidence: 89%
“…This finding is consistent with the public positions taken by the nation’s two largest unions in supporting their locals’ efforts to delay in-person learning until various public health benchmarks are met. It is also consistent with several other recent studies showing that teachers unions have influenced district reopening decisions, largely slowing the pace at which in-person learning has resumed (DeAngelis and Makridis forthcoming; Grossman et al 2021; Harris et al 2021). Although we are confident that district size is a reasonable proxy for union strength, we acknowledge that the size of a school district itself is also likely to present different logistical challenges that may shape a district’s practical choice in a reopening plan.…”
Section: Resultssupporting
confidence: 89%
“…The school reopening plan data were mainly extracted from the Education Week's dataset, which had 2020 Fall semester school reopening plans, school start dates, and last verified dates of 901 school districts [23]. We deterministically linked over 120,000 schools had been affected by closures since March 2020 [1]. In addition, despite its impacts on COVID-19 transmission and the labor market, school closure could also affect the development of children.…”
Section: Methods Data and Samplementioning
confidence: 99%
“…Moreover, the inability of many districts to negotiate reopening agreements with their local teachers’ union helped contribute to a year of entirely remote learning for a significant number of students. Unsurprisingly, several studies found that districts’ decisions about when and how much to reopen schools were influenced by local teacher-union strength (Antonucci 2021 ; DeAngelis and Makridis 2021 ; Flanders 2020 ; Grossmann et al 2021 ; Harris, Ziedan, and Hassig 2021 ; Hartney and Finger 2020 ; Marianno et al 2021 ). In one of these studies (Hartney and Finger 2020 ), the authors found a direct relationship between districts’ use of remote-only instruction and the rate of political activity (PAC donations) mobilized by the local teachers’ union.…”
Section: Why Local Education Politics Still Mattermentioning
confidence: 99%